Penggunaan Metode Waterfall dalam Perancangan Aplikasi Pemeliharaan Kendaraan Milik Daerah Berbasis WEB - Taufiq, Rohmat; Wahyudi, Septian (Program Studi Teknik Informatika Universitas Pamulang, 2023)
One of the hospital's external reporting systems is the inpatient morbidity report (RL 4a), at X Hospital it has not fully used computerization, currently inpatient morbidity reports are still being processed using Microsoft Excel which takes quite a long time and has an impact on monthly and even annual reporting . This study aims to create a planning framework to overcome the ongoing gloom at X Hospital by using Microsoft Visual Studio and Microsoft Access as information data storage using the RAD (Rapid Application Development) strategy. Descriptive qualitative research is the type of research used. The result of implementing the RAD method is to produce an inpatient morbidity information system and RL 4A reporting that makes it easier for officers to make reports, improves hospital quality and reduces delays in hospital external reporting.